Cerebellar and extracerebellar involvement in mouse eyeblink conditioning: the ACDC model - Boele, Henk-Jan; Koekkoek, S K E; De Zeeuw, Chris I. (Frontiers in Cellular Neuroscience, 2010)
Over the past decade the advent of mouse transgenics has generated new perspectives on the study of cerebellar molecular mechanisms that are essential for eyeblink conditioning. However, it also appears that results from eyeblink conditioning experiments done in mice differ in some aspects from results previously obtained in other mammals. In this review article we will, based on studies using cell-specific mouse mutants and region-specific lesions, re-examine the general eyeblink behavior in mice and the neuro-anatomical circuits that might contribute to the different peaks in the conditioned eyeblink trace. We conclude that the learning process in mice has at least two stages: An early stage, which includes short-latency conditioned responses that are at least partly controlled by extracerebellar structures such as the amygdala, and a later stage, which is represented by well-timed conditioned responses that are mainly controlled by the pontocerebellar and olivocerebellar systems. We refer to this overall concept as the Amygdala-Cerebellum-Dynamic-Conditioning Model (ACDC Model). <input id="gwProxy" type="hidden" /> <!--Session data--> <input id="jsProxy" onclick="jsCall();" type="hidden" />